2014 Kansas Performance Tests with Soybean Varieties - Schapaugh, William T., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2016)
Soybean performance tests are conducted each year to provide information on the relative performance of new and established varieties and brands at several locations in Kansas. Main Station, Manhattan William T. Schapaugh, Jr., Professor (Senior Author) Jane Lingenfelser, Assistant Agronomist Brent Christenson, Research Assistant Cheyenne Stephens, Research Assistant Research Centers Josh Coltrain, Crawford County Extension Patrick Evans, Colby Kelly Kusel, Parsons Monty Spangler, Garden City Experiment Fields Eric Adee, Topeka Gary Cramer, Hutchinson James Kimball, Ottawa Michael Larson, Belleville and Scandia Wendell Lilyhorn, Hutchinson Cooperators Vernon Egbert, McCune Lance Rezac, Onaga Dale Roberds, Pittsburg Clayton Short, Assaria
Keywords: Soybeans; Seeds; Yields; Environmental factors; Kansas